Phospholipid molecular species quantitation from mass spectra of underivatized lipids. - C G Crawford; R D Plattner (Journal of Lipid Research, 1984)
Isobutane chemical ionization of 0.05 to 5 micrograms of phospholipid volatilized from a direct exposure probe provides, in less than a minute, mass spectra from which the component molecular species can be quantitated. Molecular response factors are determined from a stable external standard mixture containing saturated molecular species; a simple series of linear equations is used to correct for isotope effect and hydrogen abstraction. An internal standard allows absolute quantitation of the sample. In cases where different molecular species have the same molecular weight, the species can be quantified by tandem mass spectrometry daughter ion analysis.